Norway spruce monoculture has lower resilience and carbon sequestration capacity than a more diverse broadleaved forest: A case study in Central Europe - Bosela, Michal; Marcis, Peter; Polťák, Dominik; Rybár, Jerguš; Fleischer sr, Peter; Fleischer jr, Peter; Gömöryová, Erika; Vido, Jaroslav; Nalevanková, Paulína; Škvarenina, Jaroslav; Homolák, Marián; Výbošťok, Jozef; et al. (Elsevier, 2025)
orway spruce (Picea abies, (L.) H.Karst) monocultures have been widely planted across Europe to meet timber demands, yet their resilience to climate change remains uncertain compared to natural mixed broadleaved forests. This study examines the long-term carbon sequestration potential, soil CO₂ and CH₄ fluxes, and microbial community dynamics in a Norway spruce monoculture and a mixed forest under increasing drought and disturbance pressures in Central Europe. Using a three-year monitoring program combined with long-term tree-ring analysis (2000–2023), we quantified seasonal and annual biomass increments, soil respiration patterns, and microbial diversity shifts. The results indicate that the severe drought of 2022 significantly reduced growth rates and soil CO₂ efflux in the monoculture, whereas the mixed forest maintained more stable growth and soil respiration. Thereafter, bark beetle outbreaks in 2023 led to rapid mortality and salvage clear-cutting in the spruce stand, triggering a sharp increase in soil CO₂ emissions and a temporary decline in CH₄ oxidation, though CH₄ uptake recovered within a year—contrary to previous studies suggesting prolonged suppression. Microbial community analysis revealed a higher proportion of ectomycorrhizal fungi in the mixed forest, while saprotrophs dominated in the spruce stand, influencing soil carbon dynamics. These findings highlight the greater resilience of mixed forests to climate stressors and suggest that the increasing vulnerability of spruce monocultures could lead to long-term carbon losses. The study underscores the need for diversified forest management strategies that enhance climate resilience and carbon sequestration stability.
Keywords: soil CO2 efflux; heterotrophic soil respiration; forest management; soil carbon emissions; CH4 uptake; climate change